Possibly scalable solar hydrogen generation with quasi-artificial leaf approach - Patra, Kshirodra Kumar; Bhuskute, Bela D.; Gopinath, Chinnakonda S. (Scientific Reports, 2017)
Any solar energy harvesting technology must provide a net positive energy balance, and artificial leaf concept provided a platform for solar water splitting (SWS) towards that. However, device stability, high photocurrent generation, and scalability are the major challenges. A wireless device based on quasi-artificial leaf concept (QuAL), comprising Au on porous TiO2 electrode sensitized by PbS and CdS quantum dots (QD), was demonstrated to show sustainable solar hydrogen (490 +/- 25 mu mol/h (corresponds to 12 ml H-2 h(-1)) from similar to 2mg of photoanode material coated over 1 cm(2) area with aqueous hole (S2-/SO32-) scavenger. A linear extrapolation of the above results could lead to hydrogen production of 6 L/h.g over an area of similar to 23 x 23 cm(2). Under one sun conditions, 4.3 mA/cm(2) photocurrent generation, 5.6% power conversion efficiency, and spontaneous H-2 generation were observed at no applied potential (see S1). A direct coupling of all components within themselves enhances the light absorption in the entire visible and NIR region and charge utilization. Thin film approach, as in DSSC, combined with porous titania enables networking of all the components of the device, and efficiently converts solar to chemical energy in a sustainable manner.

Harnessing visible-light and limited near-IR photons through plasmon effect of gold nanorod with AgTiO2 - Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2018)
The utilization of the red-green-blue (RGB) and limited near-IR photons for solar hydrogen evolution (SHE) has been reported in a single plasmonic nanocomposite. Present study describes the use of AgTiO2 (AgT) decorated with Au nanorods (AgT-AuNR) to enhance the absorption of entire visible-light and limited near-IR wavelength range in the sunlight for SHE from photocatalytic water splitting reaction. It is demonstrated that the longitudinal plasmon resonance of AuNR in AgT-AuNR induces SHE between 550 and 800 nm, whereas TiO2-AuNR or AgT shows no activity in this wavelength range. The key aspect of achieving the high photocatalytic activity of AgT-AuNR in the solar spectrum is the electronic integration among metal NPs as well as with TiO2, and the heterojunctions among them. Presence of such heterojunctions has been supported by different characterization studies. However, gold nanorod exhibits field effect and further enhances light harvesting. Although the absolute amount of energy harvested only from near-IR photons is low, when combined with high-energy visible-light photons within one sun conditions, it shows a multiplier effect rather than a simple additive effect. Likely, this is the first report, where SHE has been achieved with significant amount of light absorption at lambda >= 550 nm with a plasmonic nanocomposite.

Direct solar-to-hydrogen generation by quasi-artificial leaf approach: possibly scalable and economical device - Patra, Kshirodra Kumar; Bharad, Pradnya Arunrao; Jain, Vanshika; Gopinath, Chinnakonda S. (Journal of Materials Chemistry A, 2019)
Often, a disadvantage in one area of science may become an advantage in another area. In contrast, a successful concept in one area could work for a complementary area of research too. These two philosophies have been successfully used for solar hydrogen generation and they underscore the necessity to connect relevant concepts. We, herein, report a quasi-artificial leaf (QuAL) device in a wireless configuration with a TiO2/Mn-CdS composite and NiCu as a co-catalyst for possibly scalable as well as commercially viable solar hydrogen production under one sun conditions. The device works at no applied potential and generates 10.5 mL h(-1) (16 mL h(-1)) H-2 with Ni5Cu2.5 alloy (Pt) as a co-catalyst, which corresponds to a power conversion efficiency (PCE) of 4.8% (7.3%). The significant resemblance of NiCu alloy to Pt in terms of its electrochemical activity and electronic structure makes the device more economical. While the millisecond lifetime of electrons in Mn-CdS is known to help for white light emission, the same factor helps to greatly improve charge utilization for H-2 production in the QuAL device. In contrast, the reabsorption of emitted light is a vexing problem in emission applications; however in the present work, reabsorption is successfully utilized to enhance hydrogen yield. Spectroscopy techniques combined with electrocatalytic studies were employed and the results correlated with solar hydrogen generation, demonstrating this as a new pathway to design better solar-light-harvesting architectures.

Oxidative disproportionation of MoS2/GO to MoS2/MoO3-x/RGO : integrated and plasmonic 2D-multifunctional nanocomposites for solar hydrogen generation from near-infrared and visible regions - Patra, Kshirodra Kumar; Ghosalya, Manoj Kumar; Bajpai, Himanshu; Raj, Sreeya; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2019)
Two dimensional (2D) semiconductor materials have been recently demonstrated to be effective plasmonic materials and alternatives to costly noble metals. However, tuning the plasmon resonance of 2D semiconductors and integrating with another material or semiconductor for various applications, such as solar light harvesting, remains a challenge. Herein, we designed a simple and attractive method, which facilitates the diffusion of oxygen from the graphene oxide (GO) layers of the MoS2/GO (MG) composite to oxidize the MoS2 layers significantly due to thermal treatment under inert atmosphere. This is the key step in the formation of MoS2/MoO3-x/RGO (MMR) (x = 0, 0.5, and 1, and all stoichiometries co-exist), due to disproportionation of MoS2/GO, with bulk heterojunctions among the components. The observed behavior is attributed to the oxidation of Mo4+ cations (of MoS2) to higher oxidation states in MMR (Mo(5+ )and Mo6+ of MoO3-x), which also alters the valence-band electronic structure and work function of the resulting composite. The 2D MoO3-x layers with a large amount of Mo5+ oxidation states enables facile charge carrier generation due to plasmonic effect, whereas MoS2 provides active sites for catalysis. The solar H-2 generation was demonstrated in the visible and near-infrared region by combining both the plasmonic and catalytic effects in one composite. These results demonstrate the important role of RGO to provide energy-level alignment, charge carrier diffusion, and help to generate plasmonic effect in the composite.

Why the thin film form of a photocatalyst is better than the particulate form for direct solar-to-hydrogen conversion: a poor man's approach - Nalajala, Naresh; Patra, Kshirodra Kumar; Bharad, Pradnya A.; Gopinath, Chinnakonda S. (RSC Advances, 2019)
We demonstrated an easy method to improve the efficiency of photocatalysts by an order of magnitude by maximizing light absorption and charge carrier diffusion. Degussa titania (P25) and Pd/P25 composite photocatalyst thin films coated over regular glass plates were prepared and evaluated for solar hydrogen production in direct sunlight with aqueous methanol. It is worth noting that only UV light present in direct sunlight (similar to 4%) was absorbed by the catalysts. The hydrogen production activities of catalysts were compared for thin film and particulate forms at 1 and 25 mg levels. The hydrogen yield values suggested that 1 mg thin film form of Pd/P25 provided 11-12 times higher activity than 25 mg powder form. Comparable light absorption throughout the entire thickness of photocatalyst device and better contact of nanostructures that enabled the charge diffusion and charge utilization at redox sites are the reasons for high efficiency. While solar cells require charge carriers to diffuse through long distances of microns, they are utilized locally in an ensemble of particles (of nanometres) for hydrogen generation in photocatalyst thin films; this concept was used effectively in the present work.

Can half-a-monolayer of pt simulate activity like that of bulk pt? solar hydrogen activity demonstration with quasi-artificial leaf device - Bajpai, Himanshu; Patra, Kshirodra Kumar; Ranjan, Ravi; Nalajala, Naresh; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (ACS Applied Materials & Interfaces, 2020)
Pt is the best cocatalyst for hydrogen production. It is also well-known that the surface atomic layer is critical for catalysis. To minimize the Pt content as cocatalyst, herein we report on half-a-monolayer of Pt (0.5 theta(Pt)) decorated on earth-abundant Ni-Cu cocatalyst, which is integrated with a quasiartificial leaf (QuAL) device (TiO2/ZnS/CdS) and demonstrated for efficient solar hydrogen production. For the QuAL, TiO2 is sensitized with ZnS and CdS quantum dots by the SILAR method. The 0.5 theta(Pt)-decorated Ni-Cu shows an onset potential of 0.05 V vs reversible hydrogen electrode for the hydrogen evolution reaction, which is almost similar to that of commercial Pt/C. Photoactivity of the present QuAL device with either bulk Pt or 0.5 theta(Pt)-coated Ni-Cu cocatalyst is, surprisingly, equal. Our findings underscore that a fraction of a monolayer of Pt can enhance the activity of the cocatalyst, and it is worth exploring further for the high activity associated with atomic Pt and other noble metals.
Keywords: artificial leaf; nickel-copper; Photocatalysis; platinum; Solar hydrogen

Boosting electrochemical CO2 reduction to methane via tuning oxygen vacancy concentration and surface termination on a copper/ceria catalyst - Patra, Kshirodra Kumar; Liu, Zhu; Lee, Hojeong; Hong, Seungwon; Song, Hakhyeon; Abbas, Hafiz Ghulam; Kwon, Youngkook; Ringe, Stefan; Oh, Jihun (ACS Catalysis, 2022)
Metal oxides are a promising material for designing highly active and selective catalysts for the electrochemical reduction of carbon dioxide (CO2RR). Here, we designed a Cu/ceria catalyst with high selectivity of methane production at single-atomic Cu active sites. Using this, we report favorable design concepts that push the product selectivity of methane formation by combining detailed structural analysis, density functional theory (DFT), in situ Raman spectroscopy, and electrochemical measurements. We demonstrate that a higher concentration of oxygen vacancies on the catalyst surface, resulting from more available Cu+ sites, enables high selectivity for methane formation during CO2RR and can be controlled by the calcination temperature. The DFT calculation and in situ Raman studies indicate that pH controls the surface termination; a more alkaline pH generates hydroxylated surface motifs with more active sites for the hydrogen evolution reaction. These findings provide insights into designing an efficient metal oxide electrocatalyst by controlling the atomic structure via the reaction environment and synthesis conditions.
Keywords: copper-ceria; electrochemical CO2 reduction; electrolyte pH; gas diffusion electrode; methane production; Oxygen vacancy

CO2 electrolysis towards large scale operation: rational catalyst and electrolyte design for efficient flow-cell - Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (Chemical Communications, 2023)
The electrochemical CO2 reduction reaction (CO2RR) to renewable fuels/chemicals is a potential approach towards addressing the carbon neutral economy. To date, a comprehensive analysis of key performance indicators, such as an intrinsic property of catalyst, reaction environment and technological advancement in the flow cell, is limited. In this study, we discuss how the design of catalyst material, electrolyte and engineering gas diffusion electrode (GDE) could affect the CO2RR in a gas-fed flow cell. Significant emphasis is given to scale-up requirements, such as promising catalysts with a partial current density of >= 100 mA cm(-2) and high faradaic efficiency. Additional experimental hurdles and their potential solutions, as well as the best available protocols for data acquisition for catalyst activity evaluation, are listed. We believe this manuscript provides some insights into the making of catalysts and electrolytes in a rational manner along with the engineering of GDEs towards CO2RR.

Nanostructured Co-doped BiVO4 for efficient and sustainable photoelectrochemical chlorine evolution from simulated sea-water - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Mhamane, Nitin B.; Salgaonkar, Kranti N.; Gopinath, Chinnakonda S. (Dalton Transactions, 2023)
The co-production of hydrogen and chlorine from sea-water splitting could be a potential, sustainable and attractive route by any method. However, challenges to overcome are many, and critically, the sustainability and operating potential of the electrocatalyst are important. In this work, we report on Co-doping in the BiVO4 (Co-BV) crystal lattice and employed the same as the photoanode; Co-BV exhibits a photocurrent of 190 mu A cm(-2) at 1.1 V vs. RHE (the reversible hydrogen electrode) in the acidic sodium chloride solution (pH 2.3) under one sun illumination. The best-performing photoanode, with 0.05 mol% of Co doping (0.05 Co-BV), selectively produced active chlorine with 92% faradaic efficiency at 1.1 V vs. RHE by successfully suppressing the kinetically sluggish oxygen evolution reaction (OER) and the stability of the catalyst was demonstrated for up to 20 h. This is the lowest operating potential reported for the chlorine evolution reaction (CER), thus far. The overpotential required for CER with 0.05 Co-BV is lower than that of OER, which leads to selective CER at 1.1 V (vs. RHE). Co-doping into the BiVO4 lattice decreases the charge transfer resistance and enhances the CER kinetics due to its structural and electronic integration with the BV lattice. We demonstrate that Co-doping also improves the lifetime of the charge carrier and enhances the current density of CER and sustainability of the catalyst.

Design of Bi-functional mixed oxide electrodes for selective oxidative C-C cleavage of glycerol to formate and synchronized green hydrogen production - Saha, Arindam; Murugiah, Vasantharadevi; Ranjan, Ravi; Chauhan, Inderjeet; Patra, Kshirodra Kumar; Bajpai, Himanshu; Saha, Avisekh; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2024)
Alkaline water electrolysis is a mature method to produce green hydrogen; however, it suffers from significantly high cost as high overpotentials are required for the oxygen evolution reaction (OER). However, the OER could be avoided altogether by replacing it with kinetically favorable oxidation of abundantly available feedstock molecules at a significantly low potential to value-added product(s) together with green hydrogen generation. This is a potential method to address the high cost of green hydrogen production while converting waste to wealth. Herein, we report green, template-free hydrothermal synthesis of an electrochemically active NiCoMn mixed oxide (NCMO) electrocatalyst with multiple sites, porous structure, large surface area, and nanoneedle (NN) morphology deposited directly over Ni foam (NF). Sustainable electrocatalytic performance was demonstrated for 120 h in 0.2 M alkaline glycerol using chronoamperometry and chronopotentiometry. Highly selective formate production demonstrated an exclusive C-C cleavage with the present catalyst system. Oxides of individual metal-ions (Ni, Co, and Mn) and their bimetallic combination (NiCo, NiMn, and CoMn) exhibited lower activity and product selectivity than the trimetallic NCMO electrocatalyst. The membrane-free two-electrode electrolyzer setup with NCMO/NF at both the anode and cathode (NCMO/NF & Vert;NCMO/NF) requires 1.63 V to accomplish 100 mA cm-2 with 0.2 M glycerol, which is 296 mV less than that of 1 M KOH solution. High faradaic efficiency was observed for hydrogen (98%) with highly selective formate (90%) production. Electrocatalytic formate generation from an alkaline glycerol solution with NCMO is an energy-efficient and promising approach that also supplies carbon-negative green H2. NiCoMn oxide nanoneedles with a cactus-like morphology are shown as bifunctional electrocatalysts that selectively oxidize glycerol to HCOOH and concurrently produce H2.

Electrocatalytic and selective oxidation of glycerol to formate on 2D 3d-metal phosphate nanosheets and carbon-negative hydrogen generation - Chauhan, Inderjeet; Vijay, Pothoppurathu M.; Ranjan, Ravi; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Materials Au, 2024)
In the landscape of green hydrogen production, alkaline water electrolysis is a well-established, yet not-so-cost-effective, technique due to the high overpotential requirement for the oxygen evolution reaction (OER). A low-voltage approach is proposed to overcome not only the OER challenge by favorably oxidizing abundant feedstock molecules with an earth-abundant catalyst but also to reduce the energy input required for hydrogen production. This alternative process not only generates carbon-negative green H2 but also yields concurrent value-added products (VAPs), thereby maximizing economic advantages and transforming waste into valuable resources. The essence of this study lies in a novel electrocatalyst material. In the present study, unique and two-dimensional (2D) ultrathin nanosheet phosphates featuring first-row transition metals are synthesized by a one-step solvothermal method, and evaluated for the electrocatalytic glycerol oxidation reaction (GLYOR) in an alkaline medium and simultaneous H2 production. Co3(PO4)2 (CoP), Cu3(PO4)2 (CuP), and Ni3(PO4)2 (NiP) exhibit 2D sheet morphologies, while FePO4 (FeP) displays an entirely different snowflake-like morphology. The 2D nanosheet morphology provides a large surface area and a high density of active sites. As a GLYOR catalyst, CoP ultrathin (∼5 nm) nanosheets exhibit remarkably low onset potential at 1.12 V (vs RHE), outperforming that of NiP, FeP, and CuP around 1.25 V (vs RHE). CoP displays 82% selective formate production, indicating a superior capacity for C–C cleavage and concurrent oxidation; this property could be utilized to valorize larger molecules. CoP also exhibits highly sustainable electrochemical stability for a continuous 200 h GLYOR operation, yielding 6.5 L of H2 production with a 4 cm2 electrode and 98 ± 0.5% Faradaic efficiency. The present study advances our understanding of efficient GLYOR catalysts and underscores the potential of sustainable and economically viable green hydrogen production methodologies.

Electrocatalytic glycerol conversion: a low-voltage pathway to efficient carbon-negative green hydrogen and value-added chemical production - Chauhan, Inderjeet; Bajpai, Himanshu; Ray, Bishakha; Kolekar, Sadhu K.; Datar, Suwarna; Patra, Kshirodra Kumar; Gopinath, Chinnakonda S. (ACS Applied Materials and Interfaces, 2024)
Electrochemical glycerol oxidation reaction (GLYOR) could be a promising way to use the abundantly available glycerol for production of value-added chemicals and fuels. Completely avoiding the oxygen evolution reaction (OER) with GLYOR is an evolving strategy to reduce the overall cell potential and generate value-added chemicals and fuels on both the anode and cathode. We demonstrate the morphology-controlled palladium nanocrystals, afforded by colloidal chemistry, and their established morphology-dependent GLYOR performance. Although it is known that controlling the morphology of an electrocatalyst can modulate the activity and selectivity of the products, still it is a relatively underexplored area for many reactions, including GLYOR. Among nanocube (Pd-NC), truncated octahedron (Pd-TO), spherical and polycrystalline (Pd-PC) morphologies, the Pd-NC electrocatalyst deposited on a Ni foam exhibits the highest glycerol conversion (85%) along with 42% glyceric acid selectivity at a low applied potential of 0.6 V (vs reversible hydrogen electrode (RHE)) in 0.1 M glycerol and 1 M KOH at ambient temperature. Owing to the much favorable thermodynamics of GLYOR on the Pd-NC surface, the assembled electrolyzer requires an electricity input of only similar to 3.7 kWh/m(3) of H-2 at a current density of 100 mA/cm(2), in contrast to the requirement of >= 5 kWh/m(3) of H-2 with an alkaline/PEM electrolyzer. Sustainability has been successfully demonstrated at 10 and 50 mA/cm(2) and up to 120 h with GLYOR in water and simulated seawater.
Keywords: electrocatalysis; Glycerol; green hydrogen; nanocube; Palladium; SDG

Potential tuneable glucose oxidation to selective C6 molecules and CC cleavage, and parallel green H2 production: sustainable high current density electrolysis - Chauhan, Inderjeet; Patra, Kshirodra Kumar; Vijay, Pothoppurathu M.; Nalajala, Naresh; Mehta, Shweta; Joshi, Kavita; Ravindranathan, Sapna; Gopinath, Chinnakonda S. (Chemical Engineering Journal, 2026)
Current study elucidates the electrocatalytic efficacy of palladium-nanocubes (Pd-NCs) for the selective oxidation of glucose to value-added chemicals with concomitant hydrogen evolution. The Pd-NC catalyst demonstrated exceptional activity and product selectivity, achieving nearly quantitative glucose conversion (>99 %) with high gluconic and glucaric acid yield at low anodic overpotential (0.6 V vs. RHE) in alkaline electrolyte. At not-so-high elevated potentials (1.2 V vs. RHE), oxidative CC scission prevails, yielding shorter-chain carboxylates along with C6-acids. Reaction products are thoroughly characterized and quantitatively estimated by NMR spectral methods; NMR methods also provide CC cleavage and mechanistic pathways of glucose to various products. Complementary DFT calculations delineate the thermodynamic favorability of glucose adsorption on Pd-NC surfaces (-1.83 eV) and the exergonic oxidation pathway under applied bias, corroborating experimental product distributions. In a two-electrode electrolyzer, Pd-NC anode paired with Pt/C and Ni2P cathode demonstrates 100 mA/cm(2) at 0.99 V and 1.37 V, respectively, with 48 % reduction in energy input (26.6 kWh/kg H-2) compared to conventional alkaline electrolysis; critically, H-2 production energy is lower than the usable energy (33.3 kWh/kg H-2). Sustainable chronopotentiometric assays confirm sustainability (similar to 140 h) in alkaline as well as saline electrolytes, underscoring the system's resilience against chloride-mediated corrosion. Present work establishes a proof of concept for integrated biomass-component valorization and carbon-negative green hydrogen production, merging atomic-level mechanistic insights with scalable reactor design. Optimization of reaction parameters, including potential tuning, reaction temperature and electrolyte engineering, offers a compelling strategy to further enhance C6 and fragmented product selectivity and overall system efficiency.
Keywords: biomass valorization; electrocatalysis; energy conversion; Sustainability